2022
DOI: 10.1007/s00170-022-09644-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of laser process parameters in direct energy deposition on microstructure, layer characteristics, and microhardness of TC21 alloy

Abstract: In the present study, layers consisting of 40% Stellite-6 and 60% WC were deposited on Ti-6Al-3Mo-2Sn-2Zr-2Nb-1.5Cr-0.1Si (TC21) alloy by means of direct energy deposition (DED) technology aiming to improve the microstructure and microhardness. Five powder feeding rates ranging from 20 to 100 ɡ min−1 were applied using CW fiber-coupled diode laser with 4 kW output power. The deposited layers were analyzed via scanning electron microscopy (SEM), energy-dispersive X-ray analysis (EDX), and X-ray diffractometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The repair process for moulds encountered issues primarily linked to cracks that manifested post the DED process stage [29]. Key factors contributing to these challenges include the choice of material and the parameters of the deposition process.…”
Section: Encountered Challengesmentioning
confidence: 99%
“…The repair process for moulds encountered issues primarily linked to cracks that manifested post the DED process stage [29]. Key factors contributing to these challenges include the choice of material and the parameters of the deposition process.…”
Section: Encountered Challengesmentioning
confidence: 99%
“…In addition, compared to room temperature, the wear rate was reduced by 67.4-86.5% and oxidation wear mechanism was the main mechanism. Far from using traditional heat treatment processes to control wear characteristics of the TC21 alloy, a lot of research [14][15][16] reported the exploiting of surface modification technology and oxidation process to improve the hardness and wear resistance of the TC21 alloy.…”
Section: Modeling Of Wear Resistance For Tc21 Ti-alloy Using Response...mentioning
confidence: 99%
“…These processes are mainly related to the pulse width and pulse energy density of the femtosecond laser. This leads to significantly less damage compared to long-pulse lasers [15,16].…”
Section: Introductionmentioning
confidence: 99%